One only needs an island/Alone in a vast sea: "We refugees" - the waves of refugees of 2015/16 - Schinagl, Rosa Coco (Stellenbosch Theological Journal, 2020)
The article will demonstrate by a close reading of Hannah Arendt's article "We Refugees" published 1943 in New York City that Germany in particular has a responsibility towards refugees seeking to reach Europe by boat. By listening to the voice of a female refugee, the article will formulate four categories clarifying Arendt's request to welcome newcomers. Furthermore, this article highlights how Arendt's testimony can be transformed to act accordingly for today's so-called refugee crisis and it challenges the concepts of "volk", nations, and the efficiency of human rights.